Updating Materials and Methods of Construction Pedagogy for Digital Natives: A Critical Adaptation from Textbooks Tests and Essays to Digitally Fabricated Physical Materials Systems Models, Discursive Video Blogs, and Gamified Computational Simulation - Angus Eade (Building Technology Educators’ Society, 2025)
Charged with the responsibility of imparting essential knowledge of the materials, techniques, and processes involved in shaping the built environment, Materials and Methods of Construction courses have long been a standard component of National Architectural Accrediting Board [NAAB] core curricula guidelines. Punctuated by accelerating techno-cultural change, the recent timeframe has required a rapid sequence of course adaptations at the University of Kentucky, spurred initially by a nearly complete inaccessibility to physical learning spaces instigated by the COVID-19 pandemic and quarantine. Yet, as these immediate disruptions demanded pedagogical improvisation, a second transformation - less visible, systemic, and potentially more profound - was taking shape: the emergence of AI-enabled learning systems and alternate pathways to professional licensure. This study chronicles and analyzes two major adaptations to the courseís delivery between 2018 and 2025 and proposes a speculative third version - one that responds directly to this unfolding shift and positions architectural pedagogy in critical relation to the rise of AI-enabled learning platforms and professional credentialing reform.
Keywords: computational simulation; materials and methods; gamification